Estudio de la fertilización edáfica en la producción de biomasa en Pastos de corte del género Pennisetum sp., en el Ecuador - Villalva Varas, Diana Damaris (2020)
Pastures of the genus Pennisetum are crops that have a great potential for biomass production of adequate nutritional value and that allow increasing production per hectare, they adapt to a great diversity of soils with varieties known as pastures: Taiwan, giant or elephant, king grass, merkerón and napier among others. The application of edaphic fertilizers is a practice of great productive impact in the pastures, improving their yield, the production of dry matter, and the nutritional value of the forage, stimulating the development and nutritional quality of the pasture. When a crop is carried out, one of the first steps is to carry out a soil analysis in order to determine the nutrients that are available for the plants and thus specify the missing quantities to supply it through the application of edaphic fertilizers that allow increasing the production and quality of forage, as well as carrying capacity and production of the pasture. For the development of this work, bibliographic information was collected from books, magazines, newspapers, scientific articles, web pages, presentations, conferences and technical manuals. The information obtained was made through the analysis, synthesis and summary technique, in order for the reader to know about the importance of edaphic fertilization in the production of biomass in cut grasses of the genus Pennisetum sp. Due to the foregoing, it was determined that edaphic fertilization is intended to provide the soil with the nutrients extracted by the pastures in order that the forage production does not decline and thus guarantee the production of grass as food, being necessary to raise awareness among the rancher which must return nitrogen to the soil through the application of edaphic fertilizers in appropriate doses and times to correct deficiencies or imbalances of the nutrients that may exist in the soil